2016
DOI: 10.1007/s00024-016-1327-7
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Moduli of Malm Carbonate: A Poroelastic Correlation

Abstract: The static and poroelastic moduli of a porous rock, e.g. the drained bulk modulus, can be derived from stress-strain curves in rock mechanical tests and the dynamic moduli, e.g. dynamic Poisson's ratio, can be determined by acoustic velocity and bulk density measurements. As static and dynamic elastic moduli are different a correlation is often required to populate geomechanical models. A novel poroelastic approach is introduced to correlate static and dynamic bulk moduli of outcrop analogues samples, represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Pei et al (2018) observed an inelastic deformation during preconditioning even after 12 loading/unloading cycles before this effect disappears completely. Hassanzadegan et al (2016) made similar observations of time-dependent deformation and interpreted this behavior as creep, inelasticity or plasticity. The growth of subcritical cracks might be responsible for this time-dependent deformation under constant stress in a brittle regime (Nicolas et al 2017) that can be explained by a combination of enhanced plastic flow and pressure solution in carbonate Fig.…”
Section: Volumetric Deformationmentioning
confidence: 61%
See 3 more Smart Citations
“…Pei et al (2018) observed an inelastic deformation during preconditioning even after 12 loading/unloading cycles before this effect disappears completely. Hassanzadegan et al (2016) made similar observations of time-dependent deformation and interpreted this behavior as creep, inelasticity or plasticity. The growth of subcritical cracks might be responsible for this time-dependent deformation under constant stress in a brittle regime (Nicolas et al 2017) that can be explained by a combination of enhanced plastic flow and pressure solution in carbonate Fig.…”
Section: Volumetric Deformationmentioning
confidence: 61%
“…Regarding the investigations of carbonate rocks from the Upper Jurassic Malm reservoir of the Molasse Basin, studies have been rather limited so far. The poroelastic (static) and dynamic moduli of outcrop analogues samples were investigated by Hassanzadegan et al (2016) by the derivation of stress-strain curves in rock mechanical tests and measurement of acoustic velocities. The authors conducted drained and unjacketed poroelastic experiments at different temperatures and examined the strength of poroelastic coupling (product of Biot and Skempton coefficients), which helps to improve the link between seismicity and geomechanics in reservoir characterization.…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…A constant stress‐independent Biot coefficient as well as elastic moduli (i.e., Young's modulus and Poisson's ratio) is typically used to estimate poroelastic response of injection such as surface uplift 26 to predict reservoir's stress path 1,2,23–25,27 or model fault activation and induced seismicity 5–9,28 . However, rock physics experiments on different rock types (including sandstone, 29–35 carbonate, 29,34,36,37 and shale 38 ) show that Biot coefficient as well as elastic moduli could vary with either pore pressure or confining stress. Biot coefficient decreases with stress when pore pressure is constant and increases with pore pressure when stress is constant 30,38 .…”
Section: Introductionmentioning
confidence: 99%